The effects of Zn2+ doping on spin-Peierls transition in CuGeO3 - Yalçin, O; Aktas, B (Elsevier Science Bv, 2003)
Electron spin resonance (ESR) measurements on CuGeO3 doped with Zn2+ ions have been performed in the temperature range of 3-300 K. The ESR spectra of Cu2+ ions have been observed to be strongly temperature dependent for both pure and doped samples. The ESR line intensity exponentially vanishes below a critical temperature, T-c = 14 K, for pure CuGeO3. However, the replacement of magnetic Cu2+ by non-magnetic Zn2+ ion causes a drastic shift of T, to lower values, as well as significant increase in ESR signal intensity as the temperature is further decreased. The one-dimensional antiferromagnetic spin chain formed by Cu2+ ions is broken by Zn2+ ion, giving uncoupled spins at the end of the chains which result in an extra contribution to the spectra at lower temperatures. It is shown that the ground state of dimerized spins is singlet. (C) 2002 Elsevier Science B.V. All rights reserved.
2nd Moscow International Symposium on Magnetism (MISM 2001) -- JUN 20-24, 2001 -- MOSCOW STATE UNIV, MOSCOW, RUSSIA
Keywords: spin-Peierls transition; electron spin resonance; CuGeO3; doping effect